Characterization of Screening Strategies for Lynch Syndrome in Latin America - Campos-Segura, Anthony Vladimir (2025)
Background & Aims: In Latin America, genetic testing for Lynch syndrome (LS) has been partially implemented. Traditionally, LS diagnosis relied on the Amsterdam criteria and Bethesda guidelines, collectively known as traditional screening (TS). However, TS may miss up to 68% of LS cases. To improve detection rates, universal tumor screening (UTS) has been introduced. UTS involves screening all newly diagnosed patients with colorectal cancer for molecular markers to more effectively identify LS cases. Methods: Clinical and molecular data on 1684 patients with colorectal cancer, collected between 1999 and 2020, were provided by 24 Latin American genetic cancer registries and centers. Germline genetic testing was not consistently performed across all cases. Results: LS screening strategies were available for 72% (1209/1684) of cases, with germline testing conducted in one-quarter (304/1209) of these. Most cases (78%; n = 943) underwent UTS, primarily in Argentina, Chile, and Uruguay, whereas 22% (266/1209) were screened through TS. UTS identified deficient mismatch repair tumors in 29% (272/943) of cases. The rate of LS confirmed by sequencing was higher with UTS (53.3%; 65/122) compared with TS (47.8%; 87/182), although the difference was not statistically significant (P = .175). Conclusions: UTS is widely implemented in Latin America; however, the low detection rate of LS demonstrated in this study raises concerns about the routine use of germline genetic testing in our region. Our study provides real-world outcomes that highlight disparities in screening uptake and counseling referrals, illustrating the challenges that Latin American countries face in hereditary cancer syndrome screening. These results contribute to the rationale for designing effective screening strategies for LS, which may also be applicable to other hereditary cancer syndromes, ultimately.